Cognition and elevated blood pressure in community‐dwelling older adults with subjective cognitive decline: A cross‐sectional exploratory study. (31st December 2021) - Silva, Narlon Cassio Boa Sorte; Gill, Dawn P; Owen, Adrian M; Petrella, Robert J
Abstract: Background: The impact of blood pressure (BP) on cognition in older adults remains equivocal. We investigated the relationships between cognition (global and domain‐specific) and ambulatory blood pressure in older adults with subjective cognitive decline (SCD). Method: We conducted a cross‐sectional exploratory analysis of data collected from 230 community‐dwelling older adults (age mean [SD]: 69.3 [7.2], 57.8% female) with self‐reported SCD. We assessed global cognitive functioning, memory, concentration, planning, and reasoning using the computer‐based Cambridge Brain Sciences battery. Assessment of 24‐hour BP was performed using an automated, ambulatory BP monitoring device (SpacelabsModel 90207). Ambulatory BP was measured every 30 minutes between 6am and 10pm, and hourly between 10pm and 6am. We employed hierarchical regression models to examine associations between 24‐hour systolic BP and cognition. Further, we conducted ANCOVAs exploring dose‐response relationships by stratifying our sample using clinical cut‐offs for normal (≤120 mmHg, n = 52), preclinical (121 to 135 mmHg, n = 119), and hypertensive (>135 mmHg, n = 59) BP. All analyses were adjusted for age, sex, MoCA, years of education, and diagnosis of diabetes and/or hypertension. Result: In our sample, 24‐hour systolic BP was negatively associated with reasoning scores (unstandardized B [95% CI] = ‐0.008 [‐0.016 to ‐0.001], R 2 Change = 0.016, p = 0.028). The dose‐response analysis revealed a main group effect (F[2, 221] = 3.6, p = 0.029, ηp 2 = 0.032), with post‐hoc pairwise comparisons indicating that individuals with normal BP levels outperformed those with preclinical (mean difference [95% CI] = 0.280 [0.068 to 0.492], p = 0.010), and hypertensive (0.265 [0.021 to 0.508], p = 0.034) BP levels. The tasks adopted to assess reasoning targeted specifically grammatical reasoning, conflict resolution, and deductive reasoning, which fall under the overall scope of executive function tasks. No other relevant associations or interactions were found. Conclusion: In this sample of older adults with SCD, 24‐hour systolic BP levels above optimal clinical parameters were negatively associated with cognitive reasoning performance. Future research should investigate whether interventions that target BP control could mitigate impairment on reasoning performance.